Studies on the Q175 Knock-in Model of Huntington’s Disease Using Functional Imaging in Awake Mice: Evidence of Olfactory Dysfunction - Ferris, Craig F.; Kulkarni, Praveen; Toddes, Steven; Yee, Jason; Kenkel, William; Nedelman, Mark (Frontiers in Neurology, 2014)
BOLD imaging in awake mice was used to identify differences in brain activity between wild-type, HETzQ175 and HOMzQ175 genotypes in response to the odor of almond. The study was designed to see how alterations in the huntingtin gene in a mouse model of Huntington's disease would affect the perception and processing of almond odor, an evolutionarily conserved stimulus with high emotional and motivational valence. Moreover, the mice in this study were "odor naive" i.e. never having smelled almond or any nuts. Using a segmented, annotated MRI atlas of the mouse and computational analysis, seventeen out of one-hundred and sixteen brain regions were identified as responding differently to almond odor across genotypes. These regions included the glomerulus of the olfactory bulb, forebrain cortex, anterior cingulate, subiculum and dentate gyrus of the hippocampus, and several areas of the hypothalamus. In many cases these regions showed a gene-dose effect with HETzQ175 mice showing a reduction in brain activity from wild-type that is further reduced in HOMzQ175 mice. Conspicuously absent were any differences in brain activity in the caudate/putamen, thalamus, CA3 and CA1 of the hippocampus and much of the cortex. The glomerulus of the olfactory bulb in HOMzQ175 mice showed a reduced change in BOLD signal intensity in response to almond odor as compared to the other phenotypes suggesting a deficit in olfactory sensitivity.